Dispersion potential of asphaltene in live oil by nanoparticles - Zhuanying Zhan; Jun Ni (地质科技通报, 2023)
Objective In order to clarify the effect and mechanism of nanoparticles on inhibiting asphaltene precipitation in formation live oil formation under high temperature and high pressure. Methods In this study, by carrying out high-temperature and high-pressure solid particle detection experiment, the aggregation and precipitation characteristics of asphaltene in formation live oil under the action of SiO2 and Co3O4 nanoparticles were studied by means of laser detection, high-pressure microscopy and high-temperature and high-pressure filtration. Combined with the electron microscope scanning and thermogravimetric analysis experiments, the mechanism of nanoparticles inhibiting asphaltene precipitation was revealed. Results The results show that the initial pressure of asphaltene precipitation (AOP) decreases from 59.2 MPa to 53.4 MPa after adding SiO2 nanoparticles to the crude oil of the target reservoir.When the pressure was reduced to 35 MPa, the average particle size of asphaltene particles decreases from 8.82 μm to 5.53 μm, and the proportion of precipitation decreased from 66.4% to 46.4%. After adding Co3O4 nanoparticles, there is no obvious asphaltene precipitation above the bubble point pressure.The average particle size of asphaltene particles is only 1.65 μm under 35 MPa pressure, and the proportion of precipitation is only 13.6%. Nanoparticles can inhibit the precipitation of asphaltene molecules, slow down the aggregation rate of asphaltene particles, and reduce AOP and precipitation. Compared with SiO2, Co3O4 nanoparticles have higher asphaltene adsorption affinity and better inhibition effect. Conclusion The research results provide a basis for preventing asphaltene deposition and improving deposition damage.